Rituximab for the Treatment of IgG4-Related Tubulointerstitial Nephritis. Issue 32 (August 2015) - McMahon, Blaithin A.; Novick, Tessa; Scheel, Paul J.; Bagnasco, Serena; Atta, Mohamed G.; Raouf, Hajji.
<x xml:space="preserve">Abstract</x> Abstract Immunoglobulin type gamma 4 (IgG4)-related disease is a relatively newly described clinical entity characterized by a distinctive histopathological appearance, increased numbers of IgG4 positive plasma cells and often, but not always, elevated serum IgG4 concentrations. The most common renal manifestation of IgG4-related disease is tubulointerstitial nephritis marked with proteinuria, hematuria, decreased kidney function, hypocomplementemia, and radiologic abnormalities. Renal biopsy characteristics include dense lymphoplasmacytic tubulointerstitial nephritis that stains for IgG4, storiform fibrosis, and immune complex deposition in the interstitium and along tubule basement membranes. Treatment traditionally consists of prolonged glucocorticoids but cases refractory to glucocorticoids have been reported. We report a case of a 58-year-old Caucasian man who presented with fatigue, 50 pound weight loss, dyspnea, lymphadenopathy, and nephromegaly. The patient was first misdiagnosed as chronic interstitial nephritis secondary to renal sarcoid and was treated with repeated doses of prednisone. On his third relapse, he underwent a repeat renal biopsy and a diagnosis of IgG4-tubulointerstitial nephritis was confirmed. He was refractory to treatment with prednisone. The patient received Rituximab and had prompt sustained improvement in renal function. At 1 year post Rituximab treatment, his serum creatinine remains at baseline and imaging study revealed reduction in his kidney size. This is the first case report using Rituximab as a steroid sparing option for refractory IgG4-tubulointerstitial nephritis. More information is needed on the long-term effects of using of B-cell depleting agents for glucocorticoid resistant IgG4-tubulointerstitial nephritis.